1997
DOI: 10.1038/sj.cdd.4400217
|View full text |Cite
|
Sign up to set email alerts
|

Fas activates NF-κB and induces apoptosis in T-cell lines by signaling pathways distinct from those induced by TNF-α

Abstract: The p55 tumor necrosis factor (TNF) receptor and the Fas (CD95/APO-1) receptor share an intracellular domain necessary to induce apoptosis, suggesting they utilize common signaling pathways. To define pathways triggered by Fas and TNF-a we utilized human CEM-C7 T-cells. As expected, stimulation of either receptor induced apoptosis and TNF-ainduced signaling included the activation of NF-kB. Surprisingly, Fas-induced signaling also triggered the activation of NF-kB in T cells, yet the kinetics of NF-kB inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
(103 reference statements)
1
15
0
Order By: Relevance
“…5) differ substantially from those of TNF-␣ where maximum nuclear translocation could be seen 20 -30 min or earlier (data not shown). Our data regarding the kinetics of Fas-and TNF-induced NF-B activation confirm, in part, those of another direct comparison of Fas and TNF (9), and suggest that pathway intermediates in Fas-induced NF-B activation may differ from those of TNF or other death receptors. Another molecule which associates with the cytoplasmic region of Fas is FAP-1.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…5) differ substantially from those of TNF-␣ where maximum nuclear translocation could be seen 20 -30 min or earlier (data not shown). Our data regarding the kinetics of Fas-and TNF-induced NF-B activation confirm, in part, those of another direct comparison of Fas and TNF (9), and suggest that pathway intermediates in Fas-induced NF-B activation may differ from those of TNF or other death receptors. Another molecule which associates with the cytoplasmic region of Fas is FAP-1.…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, ligation of Fas killed these cells, and condensed and fragmented apoptotic nuclei also were immunoreactive for p65, directly dissociating the Fas-mediated NF-B activation from protection. Similarly, stimulation of TNFR or Fas on the surface of CEM-C7 T cells led not only to the activation of NF-B, but to apoptotic death of the cells (9). Most recently, EMSA, as well as microarray analyses of the transcriptional effects of anti-Fas (and TNF-␣) induction of HT29 colon carcinoma cells, confirmed activation of NF-B (p65/p50) by Fas ligation (45).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The suppression of the growth of CD34 + myeloid cells by TNF also correlated with the NF-κB activation . Apart from this, Fas activates NF-κB and induces apoptosis in T-cell lines by signaling pathways that are distinct from those induced by TNFα (Packham et al, 1997). Human melanoma cells are protected against UV-induced apoptosis through the down-regulation of NF-κB activity and Fas expression (Ivanov and Ronai, 2000).…”
Section: Pro-apoptotic Activity Of Nf-κbmentioning
confidence: 99%
“…However, there were also conflicting data showing that there was upregulation of TRAIL receptors in peripheral T cells upon activation, but these cells remained resistant to TRAIL [119]. TNF has also been suggested by some studies to play a role in AICD [126,143,144]. It was found that TCR stimulation can induce the expression of TNF [145] and antibody to TNF can partially inhibit antigen induced cell death of T cells in vivo [126].…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%